Newborn screening for disorders of fatty-acid oxidation: experience and recommendations from an expert meeting - Lindner, Martin; Hoffmann, Georg F.; Matern, Dietrich (Journal of inherited metabolic disease, 2010)
Experience with new-born screening (NBS) for disorders of fatty-acid oxidation (FAOD) is now becoming available from an increasing number of programs worldwide. The spectrum of FAOD differs widely between ethnic groups. Incidence calculations from reports from Australia, Germany, and the USA of a total of 5,256,999 newborns give a combined incidence of all FAOD of approximately 1:9,300. However, it appears to be much lower in Asians. Consequently, a significant prevalence and evidence for a clear benefit of NBS is proven for medium-chain acyl-CoA dehydrogenase deficiency (MCAD) only in countries with a high percentage of Caucasians, with very-long-chain acyl-CoA dehydrogenase deficiency (VLCAD) and long-chain 3-hydroxy acyl-CoA dehydrogenase deficiency (LCHAD) being additional candidates. The long-term benefit for many disorders has still to be evaluated and will require international collaboration, especially for the rarest disorders. Short-chain acyl-CoA dehydrogenase deficiency (SCAD) [as well as Systemic carnitine transporter deficiency (CTD) and dienoyl-CoA reductase deficiency (DE-RED)] are conditions of uncertain clinical significance, but most FAOD have a spectrum of clinical presentations (healthy-death). Confirmatory diagnostic procedures should be agreed upon to ensure international comparability of results and evidence-based modifications. The case of short-chain acyl-CoA dehydrogenase deficiency (SCAD) deficiency shows that even inclusion of conditions without a clearly known natural course may prove useful with respect to gain of knowledge and consecutive exclusion of a biochemical abnormality without clinical significance, although this line of argument implies the existence of structured follow-up programs and bears ethical controversies. As a final conclusion, the accumulated evidence suggests all FAOD should to be included into tandem mass spectrometry (MS/MS)-based NBS programs provided sufficient laboratory performance is guaranteed.